2005
DOI: 10.1155/mi.2005.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Oxidative Preconditioning on TNF‐α Release and Antioxidant‐Prooxidant Intracellular Balance in Mice During Endotoxic Shock

Abstract: Ozone oxidative preconditioning is a prophylactic approach, which favors the antioxidant-prooxidant balance for preservation of cell redox state by the increase of antioxidant endogenous systems in both in vivo and in vitro experimental models. Our aim is to analyze the effect of ozone oxidative preconditioning on serum TNF-α levels and as a modulator of oxidative stress on hepatic tissue in endotoxic shock model (mice treated with lipopolysaccharide (LPS)). Ozone/oxygen gaseous mixture which was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 40 publications
5
74
0
13
Order By: Relevance
“…Por otra parte, en simulaciones de shock endotóxico, el ozono protege a la rata disminuyendo TNF-α sanguíneo, esto se explicaría porque los antioxidantes generados por el ozono, administrado antes de la lesión, disminuyen el NF-kB y las citoquinas circulantes 39,40 .…”
Section: Discussionunclassified
“…Por otra parte, en simulaciones de shock endotóxico, el ozono protege a la rata disminuyendo TNF-α sanguíneo, esto se explicaría porque los antioxidantes generados por el ozono, administrado antes de la lesión, disminuyen el NF-kB y las citoquinas circulantes 39,40 .…”
Section: Discussionunclassified
“…De esta manera podemos ver el efecto inmunoregulador de la ozonoterapia, el cual contribuye a la disminución del proceso inflamatorio en nuestra patología 31 y a la mejoría de la función pulmonar. además, la ozonoterapia posee un poderoso efecto estimulador de las defensas antioxidantes 13,[16][17][18][19][20][21] , que impide la progresión del proceso destructivo del tejido pulmonar.…”
Section: Discussionunclassified
“…así también, en la activación de la actividad antioxidante endó-gena, como inmunoregulador, y su efecto en la elevación en sangre del 2,3 disfosfoglicerato, por esta vía. Por el contrario, la ozonoterapia no es recomendable por vía inhalatoria ya que en altas concentraciones es tóxica, sobre todo para el sistema respiratorio [13][14][15][16][17][18][19] .…”
Section: Fundamentos Del Uso De La Vía Rectal Para La Ozonoterapiaunclassified
See 1 more Smart Citation
“…It was reported that treatment with ozone released fewer endotoxins in the milk than treatment with antibiotics; further, no iatrogenic endotoxic shock occurred as an adverse effect, unlike that in the case of antibiotic treatment [10]. In addition, it has been reported that ozone may result in the downregulation of the cytotoxic activity of immunocytes [1,21,22]. Therefore, we speculated that using ozone water as an irrigation fluid during MIR as the first line of treatment for coliform mastitis was possible to reduce mortality.…”
Section: Discussionmentioning
confidence: 99%